El principe constante? Jan Lechoń and politics (after 1939) - Sobczak, Paweł (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
In the article, I focuss on the theme of the political views of Jan Lechoń during his New York exile, which emerged in his literary work, letters, and Dziennik. The main elements of the political stance of the author of Srebrne i czarne were in that time: resolute anti-communism, critical assessment of the actions of the government in exile, his declared admiration for America, and a nostalgia for the interwar period (idealising Józef Piłsudski). The discussed views of the poet exerted a considerable influence on his personal life, which was proven by the politically motivated breaking off his long-time relations with Julian Tuwim. One important problem is where to locate Lechoń’s dissatisfaction with the political changes in Poland, which he stated often, within the reasons for his suicide.